Cost Benefit Analysis of Agricultural Production in Khulna and Patuakhali Districts of Bangladesh - Ali, A M M Mostafa; Rahman, Md. Mostafizur; Rashid, Mohammad Abdur; Haque, Md. Zahidul; Sikder, Abdul Halim Farhad; Karim, A.T.M. Saidul; Saha, Champa Rani; Al Mamun, Abdullah; Mahmud, Mahdi; Azad, Mehedi; Nelson, Katherine; Vu, Trang; et al. (CGIAR Initiative on Asian Mega-Deltas, 2024)
Bangladesh is one of the largest deltas in the world, which is highly vulnerable to Natural Disasters because of its Geographical location, Flat and low-lying landscape, Population density, Poverty Illiteracy, Lack of Institutional setup, etc. In other words, Bangladesh's Physical, Social, and Economic conditions are typical of any of the most vulnerable countries to Natural Disasters in the world (M. Biswas, 2013). As the world’s seventh most climate risk-affected country, with 185 extreme events recorded and 0.38 fatalities per 100,000 inhabitants over the past two decades, Bangladesh must adapt rapidly to climate change while simultaneously accessing cleaner, more efficient technologies that support development, leverage co-benefits (such as in health, air and water quality) and limit emissions. The Intergovernmental Panel on Climate Change (IPCC) predicts that climate change-induced impacts could result in a 10% decline in rice production and a substantial 30% reduction in wheat production in Bangladesh by 2050 (IPCC, 2007).